2020
DOI: 10.1017/s1744133120000080
|View full text |Cite
|
Sign up to set email alerts
|

State strategies to address medicaid prescription spending: negotiated pricing vs price transparency

Abstract: This research longitudinally examines the association between levels of state Medicaid prescription spending and the state strategies intended to constrain cost increases: the negotiated pricing strategy, as indicated by state rebate programs, and the price transparency strategy, as indicated by state operation of All-Payer Claims Databases. The findings demonstrate evidence that state Medicaid prescription spending is influenced by the negotiated pricing strategy, especially Managed Care Organization (MCO) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…In contrast, hospitals in APCD-implementing states were likely to be less efficient than those in nonadopting states. The efficiency loss of hospitals with APCDs indicates that hospitals in states that implement APCDs may have struggled to accommodate their operations to the new environment [56]. The degree of data availability was positively related to efficiency but not statistically significant.…”
Section: Cross-sectional Time-series Tobit Regression Analysis Resultsmentioning
confidence: 95%
“…In contrast, hospitals in APCD-implementing states were likely to be less efficient than those in nonadopting states. The efficiency loss of hospitals with APCDs indicates that hospitals in states that implement APCDs may have struggled to accommodate their operations to the new environment [56]. The degree of data availability was positively related to efficiency but not statistically significant.…”
Section: Cross-sectional Time-series Tobit Regression Analysis Resultsmentioning
confidence: 95%
“…A recent study from the United States suggested that the sharing of prescription expenditure data among payers did not affect state Medicaid spending (Noh, Janousek and Park, 2021 [13]). Five studies from Brazil, India and South Africa showed no consistent price reductions arising from public price disclosure (Bangalee V and Suleman F., 2016 [14]; Bangalee and Suleman, 2015 [15]; Mattila, Babar and Suleman, 2021 [16]; Kohler et al, 2015[17]; Gotham, Barber and Hill, 2018 [18]) Price regulation and disclosure in South Africa has not been seen to have led to withdrawals of medicines from the market as it could have been anticipated (Naidoo and Suleman, 2021 [19]).…”
mentioning
confidence: 99%
“…40 The risk of withdrawal of some medicines from the Turkish market was also mentioned as a consequence of China referencing medicine prices in Türkiye, where prices are low due to the devaluation of the Turkish Lira, and trade regulations ban parallel export (Mondaq, 2022[55]). However, other experts referred to these threats as a tactic used by industry for leverage in negotiations; in fact, the adoption of price transparency policies in some countries, such as South Africa, has not been seen to have led to withdrawals of medicines from the market (Naidoo and Suleman, 2021 [19]). Some policymakers are concerned that moves towards greater price transparency could negatively impact accessibility, since companies could threaten withdrawal from markets or set prices at unaffordable levels (European Observatory on Health Systems and Policies, 2022 [11]).…”
mentioning
confidence: 99%
See 2 more Smart Citations